Emotional Intelligence and Immigrant Entrepreneurship Development: A Correlation Analysis of the Lebanese Family Entrepreneurships in Nigeria - Agbim, Kenneth Chukwujioke (International Journal of Small and Medium Enterprises, 2018)
The arrival of the first Lebanese immigrant in Lagos in 1890 has been followed by increase in the number of Lebanese immigrants in Nigeria. The immigrants get attached to their families on arrival. This is owing to the instrumental, financial, psychological and emotional supports they receive from their families to enable them assimilate into the Nigerian community. In spite of their contributions to the economic and infrastructural development of Nigeria through the family-owned immigrant entrepreneurships they have developed, no study seems to have been conducted in this area. Consequently, based on data from selected Lebanese family-owned entrepreneurships, this study examines the relationship between emotional intelligence and immigrant entrepreneurship development. The study adopted mail questionnaire survey design. The generated data through questionnaire were analyzed using Pearson’s correlation. It was found that emotional intelligence is significantly related to the dimensions of immigrant entrepreneurship development, that is, entrepreneurial intention, entrepreneurial capabilities, entrepreneurial networking and entrepreneurial success. Based on the results, the study recommends exposing new immigrants and immigrant entrepreneurs to trainings and programs that will improve their emotional intelligence, entrepreneurial behaviour, capabilities, networking attitude and success mindset. The ultimate effect of these trainings and programs is increase in the development of immigrant entrepreneurships.